Current medical diagnosis & treatment, 1996 (Appleton & Lange, 1996)
Designed to answer questions in everyday clinical practice, this work covers all apects of primary care, including gynaecology, obstetrics, urology, dermatology, psychiatry, neurology, otolaryngology, ophthalmology and nutrition. Drug information and bibliographies have been updated.